Production of rice straw hydrolysis enzymes by the fungi Trichoderma reesei and Humicola insolens using rice straw as a carbon source. (June 2017) - Kogo, Takashi; Yoshida, Yuki; Koganei, Keisuke; Matsumoto, Hitoshi; Watanabe, Taisuke; Ogihara, Jun; Kasumi, Takafumi
Highlights: Rice straw is a viable carbon source for fungal production of rice straw cellulases. T. reesei and H. insolens enzymes synergistically enhanced rice straw degradation. NH4 OH-treated rice straw in the culture medium improved T. reesei enzyme activity. Abstract: Rice straw was evaluated as a carbon source for the fungi, Trichoderma reesei and Humicola insolens, to produce enzymes for rice straw hydrolysis. The enzyme activity of T. reesei and H. insolens cultivated in medium containing non-treated rice straw were almost equivalent to the enzyme of T. reesei cultivated in Avicel medium, a form of refined cellulose. The enzyme activity of T. reesei cultivated in medium containing NH4 OH-treated rice straw was 4-fold higher than enzyme from cultures grown in Avicel medium. In contrast, H. insolens enzyme from cultures grown in NH4 OH-treated rice straw had significantly lower activity compared with non-treated rice straw or Avicel. The combined use of T. reesei and H. insolens enzymes resulted in a significant synergistic enhancement in enzymatic activity. Our data suggest that rice straw is a promising low-cost carbon source for fungal enzyme production for rice straw hydrolysis.